Bioconstrução como proposta de sistema construtismo para habitação popular aliado ao conceito de moradia digna - Nunes, Andréa Silveira Netto (2022)
Brazilian urbanization is a historical process and has generated an urban crisis and a housing crisis and along with this a growing housing deficit, which demonstrates the existing deficiencies in Brazilian housing. Based on this, and on the specificities and social particularities of the resident and their surroundings, the concept of housing is configured within the context of decent housing, to which all Brazilian citizens have the right to access. In Brazil, there are already some public housing policies, but it is important that the implementation of these housing policies is more efficient and effective so that there are sustainable alternatives for democratizing access to housing and city infrastructures for the population. To achieve this, it is necessary to present construction possibilities that can comply with these very important guidelines and that are also accessible in terms of construction technique and access to construction materials. The general objective is to define Bioconstruction techniques as a construction system, which pays attention to the sustainable cycle of processes, for popular housing, within the concept of decent housing in the context of the city of Passo Fundo and region, for each stage of the work. The research was conducted through bibliometric analysis of the topic, focus groups with people who had a relationship with the Bioconstruction construction system and the conventional construction system to define the most appropriate techniques for each phase of the work. Subsequently, a program of needs and organizational charts of technical specifications were created, in addition to the 3D modeling of a proposal for popular housing, considering the Bioconstruction construction system. This research understands Bioconstruction as a construction system applicable to popular housing in the context of the city of Passo Fundo, contributing to its greater insertion in civil construction and technical improvement.